Gravito-magnetic currents in the inflationary universe from WIMT - Bellini, Mauricio (2014)
Using the Weitzenböck representation of a Riemann-flat 5D spacetime, we study the possible existence of primordial gravito-magnetic currents from Gravito-electromagnetic Inflation (GEMI). We found that these currents decrease exponentially in the Weitzenböck representation, but they are null in a Levi-Civita representation because we are dealing with a 5D Riemann-flat spacetime without structure or torsion.